Analisis Komparatif Regulasi Pengelolaan Obat di Ritel Modern: Indonesia dan Singapura - Zahra Amalia Hanifa; Ayu Shalihat (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
The expansion of modern retail including hypermarkets, supermarkets, and minimarkets into pharmaceutical distribution enhances public access for self-medication, yet presents significant regulatory challenges regarding patient safety and product quality. This study compares the regulatory frameworks of Indonesia (Peraturan BPOM No. 5/2026) and Singapore (Health Sciences Authority guidelines) on supervising pharmaceutical products in modern retail. While both countries aim to safeguard consumers by restricting retail sales to high-safety, non-prescription drugs in original packaging, their regulatory strategies differ fundamentally. Indonesia employs a behavior-centric approach, mandating certified health support personnel at points of sale and educational warning labels on limited over-the-counter drugs. However, this model faces operational challenges due to high retail employee turnover and variable health literacy. In contrast, Singapore adopts a product-centric approach through the General Sale List (GSL), embedding built-in safety into product specifications via strict limits on active ingredient dosages and package sizes. This strategy minimizes retailer operational burdens and reliance on consumer literacy. Furthermore, Singapore features a dynamic, evidence-based reclassification mechanism and regulates innovative distribution channels like smart vending machines, whereas Indonesia maintains a static classification system focused on physical stores. In conclusion, both personnel oversight at point-of-sale and product specification standardization from manufacturers contribute significantly to establishing a safe and efficient drug distribution system in modern retail environments.